(untitled) (Orfeu, 2025)
This article begins an investigation into the interaction between Paul Ricoeur’s narrative theory and interpretative practices in music. Starting from the premise that mimesis, a process presented by the author in three stages, transcends imitation to reach figuration, configuration and refiguration, the work seeks to explore ways of representing subjective relationships from musical compositions, in which narrative mechanisms interact within the musical structure. At the heart of this connection is the question of whether it is possible, based on Paul Ricoeur’s hermeneutics, to draw up a discussion that can support the interpretative and performative act. This article therefore seeks to promote a conceptual framework for musical interpretation in which the subject understands the structural dynamics of the work and positions themselves based on their relationship with the world, escaping dichotomies of the subject vs. object type that affect analysis for performance purposes